Effect of oregano essential oil and resveratrol nanoemulsion loaded pectin edible coating on the preservation of pork loin in modified atmosphere packaging. (August 2020) - Xiong, Yun; Li, Shumin; Warner, Robyn Dorothy; Fang, Zhongxiang
Abstract: The effect of oregano essential oil (OEO) and resveratrol (RES) nanoemulsion loaded pectin (PEC) edible coating on fresh pork loin preservation under high oxygen modified atmosphere packaging (HOMAP) was investigated. OEO and RES emulsion/nanoemulsions were prepared and showed good stability at 4 °C for 15 days. The emulsion/nanoemulsions were incorporated into a pectin matrix and then applied on fresh pork loins for HOMAP storage at 4 °C. Results showed that coating with OEO and RES incorporation significantly prolonged the shelf-life of pork by minimising the pH and colour change, retarding lipid and protein oxidation, maintaining meat tenderness, and inhibiting microbial growth. In particular, the Nano-OEO-RES-PEC coating sample showed the best performance on meat preservation, which could be ascribed to its smaller particle size with enhanced preservative function and stability. The study suggested that the active nanoemulsion loaded biopolymer edible coating has great potential for fresh meat preservation. Highlights: OEO and RES active emulsions/nanoemulsions were prepared. Emulsion/nanoemulsions loaded pectin coatings were applied on fresh pork MAP. OEO and RES incorporated coatings extended the fresh pork shelf-life. Nano-OEO-RES-PEC coating showed the best performance on fresh meat preservation. Emulsion particle size affected the functionality and stability of the coating.